Penerapan Model Pembelajaran Pakem Berbasis Media Crossword Puzzle Untuk Meningkatkan Hasil Belajar IPS Kelas V SD - Vilamina, Vilamina; Hendriana, Evinna Cinda; Yanti, Lili (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2024)
This research aims to find out whether the PAKEM learning model based on crossword puzzle media has an effect on increasing the cognitive learning outcomes of class V students in social studies subjects and to find out whether the PAKEM learning model based on crossword puzzle media can improve the cognitive learning outcomes of class V students in social studies subjects. The type of research is quantitative research with a quasi-experimental method, Nonequivalent Control Group Design. The sample taken in the research was 23 VA class students. The data collection technique uses a crossword puzzle test technique. Data analysis techniques use effect size and N-Gain. The results of the research are: 1) The application of the PAKEM learning model based on crossword puzzle media has an effect on increasing the cognitive learning outcomes of class V students. This can be seen from the effect size results of 1.11, a high criterion. 2) the magnitude of the increase in students' cognitive learning outcomes after implementing the PAKEM learning model based on crossword puzzle media, this can be seen from the calculation results of the average N-Gain-=0.58, a percentage of 58% with the interpretation being quite effective and having medium criteria.